A classification of subgroups of odd unitary groups. Issue 9 (2nd September 2018) - Yu, Weibo; Li, Yaya; Liu, Hang
ABSTRACT: In this paper, under the Λ -stable rank condition, we discuss the classification of subgroups of odd unitary groups and get an analogue of Sandwich Theorem.